Lybatides from Lycium barbarum contain an unusual cystine-stapled helical peptide scaffold - Tan, Wei Liang (2018)
Cysteine-rich peptides (CRPs) of 2–6 kDa are generally thermally and proteolytically stable because of their multiple cross-bracing disulfide bonds. Here, we report the discovery and characterization of two novel cystine-stapled CRPs, designated lybatide 1 and 2 (lyba1 and lyba2), from the cortex of Lycium barbarum root. Lybatides, 32 to 33 amino acids in length, are hyperstable and display a novel disulfide connectivity with a cysteine motif of C-C-C-C-CC-CC which contains two pairs of adjacent cysteines (-CC-CC). X-ray structure analysis revealed the presence of a single cystine-stabilized (α + π)-helix in lyba2, a rare feature of CRPs. Together, our results suggest that lybatides, one of the smallest four-disulfide-constrained plant CRPs, is a new family of CRPs. Additionally, this study provides new insights into the molecular diversity of plant cysteine-rich peptides and the unusual lybatide scaffold could be developed as a useful template for peptide engineering and therapeutic development.